Pinnacle Rock from aboard the steamboat PROSPECTOR travelling up the Pelly River, Yukon Territory, August 1901. - University of Washington Libraries. Special Collections Division
Photographs taken on trip by the steamboat PROSPECTOR in August 1901. It was the first navigation of the Pelly and MacMillan Rivers by a steamboat. PH Coll 246.264 [Meed journal: "View passing Pinnacle Rock, Pelly River, Aug 1901."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number